Black males in postsecondary education : examining their experiences in diverse institutional contexts - Hilton, Adriel A.; Wood, J. Luke, 1982-; Lewis, Chance W. 1972- (Emerald Publishing Limited : IAP - Information Age Publishing, 2012)
Black Males in Postsecondary Institutions: Examining their Experiences in Diverse Institutional Contexts offers a comprehensive examination of the experiences of Black males in our nation's higher education institutions. In recognizing the role of institutions in fostering distinctive educational experiences, this volume systematically explores the status, academic achievement, and educational realities of Black men within numerous institutional types (i.e., community colleges, For-profit colleges, Liberal arts colleges, historically Black colleges and universities, ivy league institutions, religious-affiliated institutions, private institutions, Hispanic-serving institutions, research intensive institutions, and predominately White institutions). In line with a core commitment towards transformative change, chapter authors also provide recommendations for future research, policy, and practice aimed at fostering enhanced personal, academic, and career outcomes for Black men in college.
Keywords: African American men -- Education (Higher); African American male college students.; African American men -- Social conditions.; African Americans -- Education (Higher); African Americans -- Education (Graduate); Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books